Nucleotide and amino acid sequences of a coat protein of an Ukrainian isolate of Potato virus Y: comparison with homologous sequences of other isolates and phylogenetic analysis - Budzanivska, I.G.; Ovcharenko, L.P.; Kharina, A.V.; Boubriak, I.I.; Polischuk, V.P. (Вiopolymers and Cell, 2014)
Aim. Identification of the widespread Ukrainian isolate(s) of PVY (Potato virus Y) in different potato cultivars and subsequent phylogenetic analysis of detected PVY isolates based on NA and AA sequences of coat protein. Methods. ELISA, RT-PCR, DNA sequencing and phylogenetic analysis. Results. PVY has been identified serologically in potato cultivars of Ukrainian selection. In this work we have optimized a method for total RNA extraction from potato samples and offered a sensitive and specific PCR-based test system of own design for diagnostics of the Ukrainian PVY isolates. Part of the CP gene of the Ukrainian PVY isolate has been sequenced and analyzed phylogenetically. It is demonstrated that the Ukrainian isolate of Potato virus Y (CP gene) has a higher percentage of homology with the recombinant isolates (strains) of this pathogen (approx. 98.8– 99.8 % of homology for both nucleotide and translated amino acid sequences of the CP gene). The Ukrainian isolate of PVY is positioned in the separate cluster together with the isolates found in Syria, Japan and Iran; these isolates possibly have common origin. The Ukrainian PVY isolate is confirmed to be recombinant. Conclusions. This work underlines the need and provides the means for accurate monitoring of Potato virus Y in the agroecosystems of Ukraine. Most importantly, the phylogenetic analysis demonstrated the recombinant nature of this PVY isolate which has been attributed to the strain group O, subclade N:O.